Natural Coagulants as an Efficient Alternative to Chemical Ones for Continuous Treatment of Aquaculture Wastewater - Isabella T. Tomasi; Rui A. R. Boaventura; Cidália M. S. Botelho (Applied Sciences, 2025)
Aquaculture effluents are a growing source of water pollution, releasing suspended solids, organic matter, nitrogen, and phosphorus into aquatic environments. Recirculating aquaculture systems (RASs) have emerged as a more sustainable solution, allowing water to be continuously treated and reused. Within RASs, coagulation–flocculation is a key treatment step due to its simplicity and effectiveness. Tannin-based coagulants have gained attention as natural alternatives to traditional chemical agents. Although natural coagulants have been studied in aquaculture, only a few works explore their use in continuous-flow systems. This study evaluates a chestnut shell-based (CS) coagulant applied in continuous mode for the post-treatment of aquaculture effluent. The performance of CS was compared with Tanfloc, aluminum sulfate, and ferric chloride in removing color and dissolved organic carbon (DOC). At natural pH (6.5) and 50 mg·L−1, CS and Tanfloc achieved color removal of 61.0% and 65.5%, respectively, outperforming chemical coagulants. For DOC, Tanfloc and chemical coagulants removed 45–50%, while CS removed 32%. All coagulants removed over 90% of phosphorus, but nitrogen removal was limited (30–40%). These results highlight the potential of tannin-derived coagulants, particularly from agro-industrial residues, as sustainable solutions for aquaculture wastewater treatment in continuous systems.